Demonstration of 10 Gbps, all-optical encryption and decryption system utilizing SOA XOR logic gates - Jung, Young Jin; Son, Chang Wan; Lee, Seok; Gil, Sangkeun; Kim, Hyung Seok; Park, Namkyoo (SPRINGER, 2008)
An all-optical encryption system built on the basis of electrical logic circuit design principles is proposed, using semiconductor optical amplifier (SOA) exclusive or (XOR) logic gates. Numerical techniques (steady-state and dynamic) were employed in a sequential manner to optimize the system parameters, speeding up the overall design process. The results from both numerical and experimental testbeds show that the encoding/decoding of the optical signal can be achieved at a 10 Gbps data rate with a conventional SOA cascade without serious degradation in the data quality.